Chad : First Review Under the Extended Credit Facility Arrangement, and Request for a Waiver of Nonobservance of Performance Criteria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
On April 13, 2018, the Executive Board of the International Monetary Fund (IMF) completed the first review of Chad's economic performance under the program supported by an Extended Credit Facility (ECF) arrangement. Completion of this review enables the immediate disbursement of SDR 35.05 million (about USD 51 million). This brings total disbursements under the arrangement to SDR 70.1 million (about USD 99.8 million). The Board also approved the authorities' request to waive the non-observance of the continuous performance criterion on the non-accumulation of new external payments arrears, and to rephase the planned disbursements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet